Plasmodium falciparum infection and the risk of anemia in school children - Suriyani Tan; Taniawati Supali; Heri Wibowo (Universa Medicina, 2013)
BACKGROUNDAccording to the World Health Organization, malaria is the major cause of death from tropical infections in children and pregnant women. Severe anemia is a common complication of malaria, particularly malaria caused by Plasmodium falciparum. The purpose of the present study was to determine any association between Plasmodium falciparum infection and anemia in school children.METHODSThis was an observational study with cross-sectional approach. A total of 540 whole blood samples of school children after administration of anthelminthic treatment for 30 days, were collected for measurement of hemoglobin concentration and preparation of Giemsa-stained thin and thick blood smears.The species of Plasmodium was confirmed by real-time polymerase chain reaction (PCR). Chi-square and prevalence ratio (PR) tests were used to determine the relationship between Plasmodium falciparum infection and anemia.RESULTSThe prevalence of Plasmodium infection in school children of malarial endemic areas was 3.51%. There were 43 cases of anemia with 41 cases of mild anemia and 2 cases of moderate anemia. Among the 41 mild cases of anemia,Plasmodium falciparum infection was found in only 3 cases. The 2 cases of moderate anemia and the remaining 38 cases of mild anemia were not caused by Plasmodium falciparum infection. Subjects with Plasmodium falciparum infection had a 1.91-fold higher risk of suffering from anemia than subjectswithout Plasmodium falciparum infection, but not significant (PR=1.91; 95% C.I.=0.65-5.62).CONCLUSIONSPlasmodium falciparum infection did not significantly increase the risk of anemia in school children. Efforts to improve strategies for controlling anemia and malaria are needed.